Enhancing Students’ Reading Text Through Kipin School Application At SMK Bhinneka Nusantara - Salsabila; Syamsi Edi; Subadar (Samudra Publisher, 2024)
The aim of this research is to enhance students' reading abilities by leveraging technological advancements using the Kipin School application. This study uses the Classroom Action Research (CAR) method, this aims to improve the process and understand how good professional learning practices From the graph table, it can be explained that in the first cycle of meetings 1-2 the average score of the students' reading results was 67.45 out of 9 students who completed out of 20 children, it can be explained that the second cycle of meetings 3-4 with the average score of the reading test results using kipin school 80.65 out of 20 students who completed s16 students and 4 students who have not completed the student reading test. The use of digital applications provides positive results of this study can be seen in the first cycle of 20 students, only 9 students complete (45.00%) and 11 students do not complete (55.00%). while in the second cycle there were 16 students (80.00%) who completed and 4 students (20.00%) who did not complete. so that it can be concluded that the increase from cycle I and cycle II is 35.00%.